A method for preparing titanium boride composite silicon carbide ceramic by reaction sintering, the ceramic prepared thereby and applications thereof

CN122167171BActive Publication Date: 2026-10-09GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610643630.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-09
Estimated Expiration
2046-05-11

AI Technical Summary

Technical Problem

此外,杂质还可能影响TiB2-SiC陶瓷的导电性能、抗氧化性能等,限制其在高端领域的应用,例如在航空航天、精密机械等对材料性能要求极高的场景中,直接外加SiC制备的复合陶瓷往往难以达到使用标准

Benefits of technology

(1)本发明制备得到的硼化钛复合碳化硅(TiB2-SiC)陶瓷具有优异的力学性能,在室温下的维氏硬度为24~35GPa,断裂韧性为4.5~7MPa·m1 /2,抗弯强度为400~700MPa;在1200℃高温下的维氏硬度为18~25GPa,抗弯强度为300-500MPa。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122167171B_ABST
    Figure CN122167171B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ceramic materials, and discloses a method for preparing titanium boride composite silicon carbide ceramic by reaction sintering, the ceramic prepared by the method and application of the ceramic. The method comprises the following operation steps: Ti3SiC2 powder and SiB6 powder with a molar ratio of 1:1 are mixed to obtain mixed powder, ball milling medium and solvent are added, and the ceramic precursor powder is obtained through mixing, ball milling, drying and sieving; the ceramic precursor powder is loaded into a graphite mold, heated to 1650-1950 DEG C, a pressure of 20-35 MPa is set, and discharge plasma sintering is carried out in an argon environment to prepare titanium boride composite silicon carbide ceramic. The high-entropy boride composite silicon carbide ceramic has a Vickers hardness of 18-25 GPa at 1200 DEG C high temperature, and a bending strength of 300-600 MPa, and is suitable for the field of super-high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic material preparation technology, and specifically relates to a method for preparing titanium boride composite silicon carbide ceramics by reaction sintering, the ceramics made therefrom, and their applications. Background Technology

[0002] Titanium diboride (TiB2), as a typical transition metal boride ceramic, has become an indispensable high-performance structural and functional material in extreme environments due to its unique crystal structure and physicochemical properties, showing broad application prospects in many high-end fields such as aerospace, metallurgy, machinery, and energy.

[0003] In terms of core performance, TiB2 boasts a Mohs hardness of 9-9.5, second only to diamond, cubic boron nitride, and boron carbide, and far exceeding conventional ceramics such as boron oxide and silicon nitride. Its microhardness reaches 3000-4000 HV, giving it exceptional wear resistance and enabling it to maintain structural integrity under long-term friction and erosion conditions. Regarding corrosion resistance, TiB2 exhibits extremely high chemical stability, resisting the erosion of strong acids such as concentrated hydrochloric acid and sulfuric acid, while also resisting the erosion and corrosion of molten metal, maintaining stable performance even in complex corrosive environments. Its oxidation resistance and high-temperature resistance are also outstanding advantages. With a melting point as high as 3225℃ and an operating temperature stably maintained above 1800℃, it forms a dense oxide protective layer in high-temperature oxidizing atmospheres, effectively preventing further oxidation of internal materials. Compared to traditional SiC or MoSi2 heating elements, TiB2 heating elements offer superior performance and are suitable for various oxidizing and reducing atmospheres. Furthermore, TiB2 maintains high mechanical strength even at high temperatures, with high-temperature strength far exceeding that of most ceramic materials. It is also less prone to high-temperature creep and deformation. These combined characteristics make it suitable for various extreme and demanding working environments. Based on these excellent properties, TiB2's applications are highly focused on key components in extreme environments, making it well-suited for use in high-temperature kiln furniture, combustion nozzles, heat exchangers, sealing rings, aircraft nose cones, and other extreme applications.

[0004] TiB2 possesses irreplaceable advantages in extreme environment applications due to its excellent comprehensive properties. However, the strong covalent bonds between borides lead to drawbacks during its preparation, such as low self-diffusion coefficient and difficulty in sintering densification. To address the challenge of TiB2 sintering densification, current research generally employs a modification strategy involving the addition of a second phase. By introducing suitable second-phase materials, the sintering characteristics of TiB2 are improved, promoting atomic diffusion and densification. Among numerous second-phase additives, silicon carbide (SiC) is one of the most commonly used materials due to its high hardness, high melting point, good chemical stability, and good compatibility with TiB2's thermal expansion coefficient and mechanical properties. TiB2-SiC composite ceramics have become a current research hotspot for TiB2-based composite materials. The addition of SiC not only effectively lowers the sintering temperature of TiB2 and promotes sintering densification but also synergistically enhances the mechanical properties and oxidation resistance of the composite ceramic. For example, SiC can effectively inhibit TiB2 grain growth, promote the formation of rod-shaped TiB2 microstructures, and thus enhance the material's toughness and hardness.

[0005] However, existing TiB2-SiC ceramic preparation technologies still have significant drawbacks. Current mainstream processes all employ traditional sintering methods (such as pressureless sintering and hot-pressing) to directly add SiC particles. While this direct addition method is relatively simple and low-cost, it has unavoidable technical limitations. Impurities (such as Fe, O, and C) are easily introduced during the preparation, storage, transportation, and mixing of SiC particles with TiB2 powder. These impurities remain within the composite ceramic as oxides and carbides. Furthermore, the interfacial bonding between directly added SiC particles and the TiB2 matrix is ​​poor, easily leading to particle agglomeration and segregation, resulting in an inhomogeneous internal structure and interfacial defects in the composite ceramic. These impurities and interface defects have a significant negative impact on the performance of TiB2-SiC ceramics, especially severely weakening their mechanical properties. Impurities become sources of crack initiation and propagation, reducing the fracture toughness, flexural strength, and hardness of the composite ceramic, making it prone to fracture and breakage under stress. Simultaneously, the presence of impurities compromises the material's density, reducing its corrosion resistance and high-temperature resistance, significantly shortening the lifespan of the composite ceramic in extreme environments. Studies have shown that TiB2-SiC ceramics prepared using SiC abrasive powder with a high impurity content begin to show a decrease in strength at 600℃, while using SiC powder with a lower impurity content can maintain the material's strength up to 1400℃. Furthermore, impurities may also affect the electrical conductivity and oxidation resistance of TiB2-SiC ceramics, limiting their application in high-end fields. For example, in aerospace and precision machinery applications where material performance requirements are extremely high, composite ceramics prepared by directly adding SiC often fail to meet the applicable standards.

[0006] Therefore, developing novel preparation processes, avoiding impurity incorporation, and optimizing interfacial bonding have become key research directions for TiB2-based composite materials, which are of great significance for promoting the application of TiB2 materials in high-end extreme environments. Summary of the Invention

[0007] To address the shortcomings and deficiencies in the existing technology, the primary objective of this invention is to provide a method for preparing titanium boride composite silicon carbide (TiB2-SiC) ceramics by reaction sintering. This method employs reaction sintering, using SiB6 and Ti3SiC2 as raw materials, and utilizes spark plasma sintering. By adjusting the temperature and holding time, titanium boride composite silicon carbide ceramics are prepared.

[0008] Another object of the present invention is to provide a titanium boride composite silicon carbide (TiB2-SiC) ceramic prepared by the above method, which has excellent mechanical properties.

[0009] Another object of the present invention is to provide the application of the above-mentioned titanium boride composite silicon carbide (TiB2-SiC) ceramic.

[0010] The objective of this invention is achieved through the following technical solution: A method for preparing titanium boride composite silicon carbide ceramics by reaction sintering includes the following steps: mixing Ti3SiC2 powder and SiB6 powder in a molar ratio of 1:1 to obtain a mixed powder, then adding ball milling media and solvent, and performing ball milling, drying, and sieving to obtain ceramic precursor powder; loading the ceramic precursor powder into a graphite mold, heating to 1650~1950℃, setting the pressure to 20~35MPa, and performing spark plasma sintering in an argon atmosphere to prepare titanium boride composite silicon carbide ceramics.

[0011] The milling media is Si3N4 milling ball or WC milling ball; the solvent is anhydrous ethanol; and the sieve mesh size is 80~1000 mesh.

[0012] The particle size of both Ti3SiC2 powder and SiB6 powder is 0.5~5µm, and the purity is ≥99.999wt%.

[0013] The mass ratio of the ball milling media, solvent, and mixed powder is 5:3:1.

[0014] The heating rate is 50~150 ℃ / min, and the discharge plasma sintering time is 5~20 min.

[0015] The temperature is increased to 1750℃; the preferred time for the discharge plasma sintering is 10 minutes. A titanium boride composite silicon carbide ceramic was prepared by the above method. The titanium boride composite silicon carbide ceramic exhibits a Vickers hardness of 24–35 GPa and a fracture toughness of 4.5–7 MPa·m at room temperature. 1 / 2 Its bending strength is 400~700MPa; its Vickers hardness at 1200℃ is 18~25GPa, and its bending strength is 300-600MPa.

[0016] The above-mentioned titanium boride composite silicon carbide ceramics are used in ultra-high temperature environments.

[0017] The ultra-high temperature is above 1200℃.

[0018] The present invention prepares titanium boride composite silicon carbide (TiB2-SiC) ceramics based on the following reaction formula: Ti3SiC2+SiB6=3TiB2+2SiC. The reaction between Ti3SiC2 and SiB6 is an exothermic reaction, which creates conditions for preparing dense titanium boride composite silicon carbide ceramics under low temperature conditions.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The titanium boride composite silicon carbide (TiB2-SiC) ceramic prepared by this invention has excellent mechanical properties, with a Vickers hardness of 24~35 GPa and a fracture toughness of 4.5~7 MPa·m at room temperature. 1 / 2 Its bending strength is 400~700MPa; its Vickers hardness at 1200℃ is 18~25GPa, and its bending strength is 300-500MPa.

[0020] (2) This invention uses Ti3SiC2 powder and SiB6 powder for reaction sintering, replacing the traditional process of directly adding SiC particles for sintering, which fundamentally solves the problems of impurity incorporation and poor interfacial bonding. Ti3SiC2 has the characteristics of both metal and ceramic, with high electrical conductivity, thermal stability and excellent damage resistance. Its purity is easy to control, which can effectively avoid the introduction of foreign impurities. As a high-quality boron and silicon source, SiB6 can react synergistically with Ti3SiC2 during high-temperature sintering to generate TiB2 and SiC in situ without the need for additional SiC particles, thus fundamentally eliminating the possibility of impurity incorporation during the preparation, storage and mixing of SiC particles. At the same time, during the reaction sintering process, the SiC particles generated in situ are uniform in size and well dispersed, forming a tight interfacial bond with the TiB2 matrix, effectively avoiding interfacial defects such as particle agglomeration and segregation, and significantly optimizing the internal structure of the composite ceramic. Furthermore, the reactive sintering of Ti3SiC2 and SiB6 can utilize the chemical energy released during the reaction as a driving force for sintering, thereby lowering the sintering temperature and shortening the sintering time. This further promotes the densification of TiB2, significantly improving the density of the sintered body compared to traditional sintering processes. Simultaneously, it synergistically improves the mechanical properties and high-temperature resistance of the composite ceramic. This novel reactive sintering process not only solves the core bottleneck of difficult TiB2 densification but also overcomes the inherent defects of traditional SiC addition processes. It provides a new pathway for the large-scale, high-performance preparation of TiB2-based composite materials, and is of great significance for promoting the application of TiB2 materials in high-end extreme environment fields. Attached Figure Description

[0021] Figure 1 The image shows a SEM image of TiB2-SiC ceramics obtained by holding at 1750℃ for 10 min.

[0022] Figure 2 The image shows a SEM image of TiB2-SiC ceramics obtained by holding at 1850℃ for 10 min.

[0023] Figure 3 The image shows a SEM image of TiB2-SiC ceramics obtained by holding at 1950℃ for 10 min.

[0024] Figure 4 This is a phase equilibrium diagram of TiB2-SiC ceramics at 25~2000℃. Detailed Implementation

[0025] The present invention will be further described below with reference to specific embodiments, but these should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.

[0026] The Ti3SiC2 powder and SiB6 powder used in the following examples have a particle size of 0.5~5µm and a purity of ≥99.999wt%.

[0027] Example 1

[0028] Ti3SiC2 powder and SiB6 powder were mixed in a molar ratio of 1:1 to obtain a mixed powder. Then, Si3N4 grinding balls and anhydrous ethanol (99.99% purity) were added as milling media. After mixing, ball milling, drying, and sieving through a 200-mesh sieve, ceramic precursor powder was obtained. The mass ratio of Si3N4 grinding balls, anhydrous ethanol, and the mixed powder was 5:3:1. The ceramic precursor powder was loaded into a graphite mold, heated to 1750℃ at a rate of 150℃ / min, and subjected to spark plasma sintering at a pressure of 30MPa under argon atmosphere for 10 min to prepare titanium boride composite silicon carbide (TiB2-SiC) ceramic. The SEM image of the obtained TiB2-SiC ceramic is shown below. Figure 1 As shown, the TiB2-SiC ceramic exhibits no obvious voids, indicating a high degree of densification. Furthermore, the grain size of both titanium boride and silicon carbide is less than 1 µm, forming submicron-scale TiB2-SiC ceramics. Figure 4 As shown, at 1750℃, the phase equilibrium products are TiB2 and SiC phases.

[0029] The TiB2-SiC ceramic prepared in this embodiment exhibited a Vickers hardness of 35 GPa (Hv0.2) and a fracture toughness of 7 MPa·m at room temperature. 1 / 2 The bending strength is 700MPa; the Vickers hardness at 1200℃ is 25GPa (Hv0.2), and the bending strength is 600MPa.

[0030] Example 2

[0031] Ti3SiC2 powder and SiB6 powder were mixed in a molar ratio of 1:1 to obtain a mixed powder. Then, Si3N4 grinding balls and anhydrous ethanol (99.99% purity) were added as milling media. After mixing, ball milling, drying, and passing through a 200-mesh sieve, ceramic precursor powder was obtained. The mass ratio of Si3N4 grinding balls, anhydrous ethanol, and the mixed powder was 5:3:1. The ceramic precursor powder was loaded into a graphite mold, heated to 1850℃ at a rate of 150℃ / min, and subjected to spark plasma sintering at a pressure of 30MPa under argon atmosphere for 10 min to prepare titanium boride composite silicon carbide (TiB2-SiC) ceramic. The SEM image of the obtained TiB2-SiC ceramic is shown below. Figure 2 As shown, TiB2-SiC ceramics exhibit no obvious pores, indicating a high degree of densification; furthermore, titanium boride forms a rod-like structure, while silicon carbide displays an irregular morphology. Figure 4 As shown, at 1850℃, the phase equilibrium products are TiB2 and SiC phases.

[0032] The TiB2-SiC ceramic prepared in this embodiment exhibited a Vickers hardness of 30 GPa (Hv0.2) and a fracture toughness of 5 MPa·m at room temperature. 1 / 2 The bending strength is 550MPa; the Vickers hardness at 1200℃ is 22GPa (Hv0.2), and the bending strength is 500MPa.

[0033] Example 3

[0034] Ti3SiC2 powder and SiB6 powder were mixed in a molar ratio of 1:1 to obtain a mixed powder. Then, Si3N4 grinding balls and anhydrous ethanol (99.99% purity) were added as milling media. After mixing, ball milling, drying, and passing through a 200-mesh sieve, ceramic precursor powder was obtained. The mass ratio of Si3N4 grinding balls, anhydrous ethanol, and the mixed powder was 5:3:1. The ceramic precursor powder was loaded into a graphite mold, heated to 1950℃ at a rate of 150℃ / min, and subjected to spark plasma sintering at a pressure of 30MPa under argon atmosphere for 10 min to prepare titanium boride composite silicon carbide (TiB2-SiC) ceramic. The SEM image of the obtained TiB2-SiC ceramic is shown below. Figure 3 As shown, TiB2-SiC ceramics exhibit no obvious pores, indicating a high degree of densification; furthermore, titanium boride forms a rod-like structure, while silicon carbide displays an irregular morphology. Figure 4 As shown, at 1950℃, the phase equilibrium products are TiB2 and SiC phases.

[0035] The TiB2-SiC ceramic prepared in this embodiment exhibited a Vickers hardness of 24.5 GPa (Hv0.2) and a fracture toughness of 4.5 MPa·m at room temperature. 1 / 2 The bending strength is 400 MPa; the Vickers hardness at 1200℃ is 18 GPa (Hv0.2), and the bending strength is 300 MPa.

[0036] In summary, the titanium boride composite silicon carbide prepared by the reaction sintering method of this invention exhibits good mechanical properties, with a Vickers hardness of 24-35 GPa and a fracture toughness of 4.5-7 MPa·m at room temperature. 1 / 2 Its bending strength is 400~700MPa; its Vickers hardness at 1200℃ is 18~25GPa, and its bending strength is 300-600MPa. It can be well applied in ultra-high temperature extreme environment fields, such as aerospace power field, metallurgical high temperature extreme working conditions, energy equipment high temperature field, military or special protection field.

[0037] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing titanium boride composite silicon carbide ceramics by reaction sintering, characterized in that... The process includes the following steps: Ti3SiC2 powder and SiB6 powder with a molar ratio of 1:1 are mixed together to obtain a mixed powder. Then, ball milling media and solvent are added, and the mixture is ball milled, dried, and sieved to obtain ceramic precursor powder. The ceramic precursor powder is loaded into a graphite mold, heated to 1650~1950℃, and the pressure is set to 20~35MPa. Under an argon atmosphere, spark plasma sintering is performed to prepare titanium boride composite silicon carbide ceramic. The phase equilibrium products are TiB2 and SiC phases. The heating rate is 50~150 ℃ / min, and the discharge plasma sintering time is 5~20 min.

2. The method for preparing titanium boride composite silicon carbide ceramics by reaction sintering according to claim 1, characterized in that: The milling media is Si3N4 milling ball or WC milling ball; the solvent is anhydrous ethanol; and the sieve mesh size is 80~1000 mesh.

3. The method for preparing titanium boride composite silicon carbide ceramics by reaction sintering according to claim 1, characterized in that: The particle size of both Ti3SiC2 powder and SiB6 powder is 0.5~5µm, and the purity is ≥99.999wt%.

4. The method for preparing titanium boride composite silicon carbide ceramics by reaction sintering according to claim 1, characterized in that: The mass ratio of the ball milling media, solvent, and mixed powder is 5:3:

1.

5. The method for preparing titanium boride composite silicon carbide ceramics by reaction sintering according to claim 1, characterized in that: The temperature is raised to 1750°C; the discharge plasma sintering time is 10 minutes.

6. A titanium boride composite silicon carbide ceramic prepared by the method according to any one of claims 1 to 5, characterized in that: The titanium boride composite silicon carbide ceramic has a Vickers hardness of 24-35 GPa and a fracture toughness of 4.5-7 MPa·m at room temperature. 1 / 2 Its bending strength is 400~700MPa; its Vickers hardness at 1200℃ is 18~25GPa, and its bending strength is 300-600MPa.

7. The application of the titanium boride composite silicon carbide ceramic according to claim 6 in ultra-high temperature environments above 1200℃.

Citation Information

Patent Citations

  • SiC-HfB2 composite ceramic as well as preparation method and application thereof

    CN119638435A

  • Sintered silicon carbide-titanium diboride mixtures and articles thereof

    US4327186A